(untitled) (The Peerian Journal, 2023)
The paper deals with the use of effective innovative pedagogical technologies in the process of professional musical training of students, which will improve the level of training of specialists in the field of musical art. Application of pedagogical technologies and their functions in the process of music training with the purpose of upgrading the quality of future professional musicians’ training is presented.